Vitamin E requirements of dairy calves - Reddy, P.G.; Morrill, J.L.; Minocha, H.C.; Frey, R.A.; Stevenson, Jeffrey S. (Kansas Agricultural Experiment Station, 2012)
Thirty-two Holstein heifer calves receiving conventional rations were supplemented with 0 (control), 125, 250, or 500 IU vitamin E/calf/day. The objective was to determine the optimum requirement based on their performance from birth to 24 wk of age. Results on weight gains, feed consumption, serum enzymes indicative of cell membrane damage, immune responses, and metabolic profile indicated that supplementation of calves receiving conventional rations with 125 to 250 IU/day may maximize their performance.
Keywords: Dairy; Vitamin E; Weight gain; Feed consumption; Performance